Neuroprotective Potential of Marrubium vulgare Linn. Extract against Scopolamine-Induced Alzheimer’s Type Dementia in Mice - Verma, Yogesh; Kalra, Sunishtha; Sachdeva, Himanshu; Kumar, Praveen; Singh, Govind (Indian Journal of Pharmaceutical Education and Research, 2025)
Background Alzheimer's Disease (AD) is a progressive neurodegenerative disorder characterized by memory impairment, cognitive decline and behavioural changes. It primarily affects individuals over the age of 65. It poses a substantial global health burden, with an increasing prevalence among the elderly population. Although the exact aetiology of AD is complex and multifactorial, emerging evidence suggests that dysfunction of glutamatergic neurotransmission, particularly involving the N-Methyl-D-Aspartate (NMDA) receptors, plays a crucial role in the pathophysiology of AD. Materials and Methods Fresh plant material was collected, extracted and administered orally to experimental groups, the negative control group received scopolamine, while the control group received a vehicle. Behavioural assessments, biochemical assays, neurotransmitters and histo-pathological examinations were conducted. Results Scopolamine administration significantly increased glutamatergic activity in the brain regions of mice, while Marrubium vulgare treatment mitigated this effect in a dose-dependent manner. Moreover, scopolamine-induced memory deficits were associated with elevated glutamate levels and oxidative stress, as indicated by decreased levels of glutathione and increased levels of malondialdehyde, superoxide dismutase and catalase. Treatment with Marrubium vulgare attenuated the scopolamine-induced oxidative stress by reducing glutamate and MDA levels and restoring GSH, catalase and SOD levels in the brain. Conclusion These findings suggest that Marrubium vulgare exerts its memory-enhancing effects by modulating glutamatergic activity and reducing oxidative stress in this scopolamine-induced dementia model. Targeting these mechanisms may contribute to developing new AD therapies. Further research is needed to elucidate the molecular pathways and validate the potential clinical utility of Marrubium vulgare for AD management.
Keywords: Alzheimer’s Disease; Glutamate; Neurotransmitter; Oxidative stress; Marrubium vulgare